THE SERVICE POTENTIAL CONCEPT AND INTER-PERIOD TAX ALLOCATION. - Drake, David F. (The Accounting Review, 1962)
The problem of inter-period tax allocation arises from a basic misunderstanding of depreciation. The "allocators" have implicitly assumed that depreciation is not a function of the federal government's income tax policy, that is, the same pattern of depreciation is assumed to be "proper" before and after the availability of accelerated depreciation. The service potential concept implicitly recognizes a "tax liability," and in terms of its present value. The present value of the tax outflow is equivalent to a liability in that it is an offset to asset value. Therefore, any attempt to recognize another liability in the financial reports represents a form of double-counting. The market process of assigning prices to assets already takes full cognizance of the stream of future tax payments. Taxes should be treated as an ordinary expense of the period in which they are incurred. This disposition will provide no theoretical problems if the depreciation pattern "properly" reflects the stream of service potential. In other words, income taxes have two properties, they are a "period" expense, and they represent an important determinant of the pattern of depreciation.